Inhalable ciprofloxacin/polymyxin B dry powders in respiratory infection therapy - Zhengqi Xu; Hriday Bera; Hengzhuang Wang; Junwei Wang; Dongmei Cun; Yu Feng; Mingshi Yang (Acta Materia Medica)
The current study focused on the formulation, physicochemical characterization, and antibacterial susceptibility testing of inhalable spray dried powders containing ciprofloxacin (CIP) and polymyxin B sulfate (PMB). CIP nanosuspensions with an average particle diameter of 435.9 ± 9.3 nm were initially obtained using the wet-milling protocol and subsequently co-spray dried with PMB solutions to yield inhalable dry powders. The Powder X-Ray Diffraction (P-XRD) results showed that the wet-milled CIP nanoparticles were in a 4.8 hydrate state, which were transformed to 3.7 hydrates and amorphous materials after co-spray drying. The PMB remained in an amorphous state in the dry powders. Differential Scanning Calorimetry (DSC) analyses revealed that the glass transition temperatures (T g s) of the co–spray dried formulations were higher than the T g of CIP, but lower than the T g of PMB. Fourier Transform Infrared Spectrometer (FTIR) studies suggested the existence of π - π interactions between CIP and PMB in the co-spray dried powders. These powders also retained antimicrobial effects against Pseudomonas aeruginosa strain PAO1. In addition, the spray-dried powder formulations exhibited satisfactory solid-state stability and aerodynamic characteristics when stored under 3% relative humidity and 20 ± 5 °C for 4 months. Overall, the newly developed inhalable CIP/PMB dry powders are a promising therapeutic strategy for respiratory tract infections.